2004
DOI: 10.1185/030079904x6273
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, comparative study of rivastigmine, donepezil and galantamine in a real-world setting

Abstract: This is the first study to compare the effects of the three most commonly-used cholinesterase inhibitors on the MMSE, ADAS-cog, IADL and ADL. Limitations included its small population size, its open-label design, and the fact that patients were randomised only after the introduction of galantamine. There were no statistically significant differences between the three drugs at 3 months. While numerical trends were observed suggesting the effect of rivastigmine > donepezil > galantamine, larger, longer-term pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 10 publications
1
26
0
2
Order By: Relevance
“…In terms of cognitive function and functionality of treated patients, some studies have shown similar results among the 3 ChEIs [33,37,38] , while other studies have shown a significant advantage for one of them: rivastigmine [36,39,40] , galantamine [34] or donepezil [35,40] . However, no strict comparisons have been done with memantine.…”
Section: Discussionmentioning
confidence: 85%
“…In terms of cognitive function and functionality of treated patients, some studies have shown similar results among the 3 ChEIs [33,37,38] , while other studies have shown a significant advantage for one of them: rivastigmine [36,39,40] , galantamine [34] or donepezil [35,40] . However, no strict comparisons have been done with memantine.…”
Section: Discussionmentioning
confidence: 85%
“…However, very few and not conclusive comparative clinical trials have been performed with the different AChEIs currently used to treat Alzheimer's disease. The study by Aguglia et al (2004) is the first to compare the effects of donepezil, rivastigmine, and galantamine on the Mini-Mental State Examination, Alzheimer's Disease Assessment Scale-cogntive subscale, Instrumental Activities of Daily Living, and Activities of Daily Living; however, limitations of the study included its small population size, its open-label design, and the fact that patients were randomized only after the introduction of galantamine. The results of this study showed no statistical significant differences between the three drugs at 3 months, although numerical trends were observed that suggested the effect of rivastigmine Ͼ donepezil Ͼ galantamine.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the six prospective studies reported data from the CRONOS project, a national project initiated by the Italian government in October 2000 [26,27,31,32] . The project involved 503 Alzheimer evaluation units (AEUs) and aimed to standardise ChEI prescriptions and to assess their effects on defined outcomes (cognition, functional status, behaviour) in non-selected subjects with mild to moderate AD [35] .…”
Section: Prospective Study Characteristicsmentioning
confidence: 99%
“…The project involved 503 Alzheimer evaluation units (AEUs) and aimed to standardise ChEI prescriptions and to assess their effects on defined outcomes (cognition, functional status, behaviour) in non-selected subjects with mild to moderate AD [35] . No restrictions on which ChEI was prescribed were applied in 3 of the 4 studies [26,27,31,32] , although galantamine only became available for treatment from April 2001 onwards. However, in the study by Aguglia et al [31] , treatment was assigned in a pseudo-randomised fashion based on arrival at the AEU following the availability of galantamine.…”
Section: Prospective Study Characteristicsmentioning
confidence: 99%